The hidden pathways to internalized weight bias: from insecure attachment to depressive self-schemas - Bianciardi, Emanuela; Quinto, Rossella Mattea; Longo, Ester; De Angelis, Federica; Siracusano, Alberto; Niolu, Cinzia; Di Lorenzo, Giorgio (Frontiers in Psychiatry, 2025)
BackgroundInternalized weight bias (IWB) is associated with adverse physical and psychopathological outcomes, yet the cognitive and emotional mechanisms underlying its development in non-clinical populations remain insufficiently understood. This study examined whether attachment insecurity, depressive symptoms, and alexithymia were related to IWB in adults with overweight/obesity, and tested a parallel mediation model of depressive symptoms and alexithymia in the link between attachment insecurity and IWB.Methods194 Italian adults (75% female; Mage = 37.6, SD = 14.7; BMI ≥ 25) completed an online survey including self-report measures of IWB, attachment style, depression, alexithymia, eating disorder risk, and body dissatisfaction. Hierarchical regression models were conducted to identify predictors of IWB, followed by mediation analyses (PROCESS Model 4) to test indirect effects.ResultsThe final regression model explained 74% of the variance in IWB. Significant predictors included body dissatisfaction (β = .43, p <.001), cognitive depressive symptoms (β = .22, p <.001), and anxious attachment (β = .30, p <.001). Difficulty describing feelings was unexpectedly inversely associated with IWB (β = –.11, p = .04). Mediation analyses revealed that cognitive depressive symptoms partially mediated the relationship between anxious attachment and IWB, whereas alexithymia dimensions did not.ConclusionFindings highlighted cognitive depressive symptoms as a central pathway linking insecure attachment to IWB, while suggesting a paradoxical protective role for alexithymic difficulties in emotional expression. We emphasized the importance of considering individual vulnerability factors—particularly relational insecurity and depressive cognitions—in theoretical models of IWB and in the design of targeted clinical interventions.